2020
DOI: 10.1371/journal.pone.0233256
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anti-hepatitis E virus IgG antibodies in sera from hemodialysis patients in Tripoli, Lebanon

Abstract: Hepatitis E virus (HEV) is an important global public health concern. Several studies reported a higher HEV prevalence in patients undergoing regular hemodialysis (HD). In Lebanon, the epidemiology of HEV among HD patients has never been investigated previously. In this study, we examine the seroprevalence of HEV infection among 171 HD patients recruited from three hospital dialysis units in Tripoli, North Lebanon. Prevalence of anti-HEV IgG antibodies was evaluated in participant's sera using a commercial enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
0
5
1
Order By: Relevance
“…In the context of investigating the utilization of various water sources, a logistic regression analysis revealed a significant association between the consumption of bottled water and a reduced probability of HEV-positive cases (OR = 0.20, 95% CI: 0.04-0.99). This finding contrasts with the observations made by researchers in Croatia and Lebanon, who did not identify a similar relationship [15,16].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the context of investigating the utilization of various water sources, a logistic regression analysis revealed a significant association between the consumption of bottled water and a reduced probability of HEV-positive cases (OR = 0.20, 95% CI: 0.04-0.99). This finding contrasts with the observations made by researchers in Croatia and Lebanon, who did not identify a similar relationship [15,16].…”
Section: Discussioncontrasting
confidence: 99%
“…The Euroimmun was selected based on its established high specificity of 100% for anti-HEV IgM and 99.3% for anti-HEV IgG in patients lacking markers of HEV infection, as observed in our study population [14]. Additionally, other authors have utilized Euroimmun to assess the prevalence of anti-HEV among different patient groups [9,[15][16][17].…”
Section: Serological Testingmentioning
confidence: 99%
“…The seroprevalence of IgG anti-HEV antibodies (12.82%) reported in our study was similar to the seroprevalence reported in Uruguay (10%) and China (13.36%) (13,29), but remarkably lower than those reported in other countries such as Sudan (56.4%), France (54.4%), Central Italy (49%), South Africa (42.8%), Nepal (41.9%), Dutch (31%) and the Netherlands (27%) (5,10,11,15,27,28,30). Recently, two studies have been conducted in Lebanon to evaluate the anti-HEV IgG seropositivity in different high-risk populations such as pregnant women and hemodialysis patients (9,31). Surprisingly, our results revealed higher anti-HEV IgG seropositivity as compared to pregnant women (0.22%), but lower than the seroprevalence reported in hemodialysis patients (21.63%).…”
Section: Discussionmentioning
confidence: 87%
“…A re-cent report in Lebanon has examined the prevalence of IgG anti-HEV antibodies in sera of hemodialysis patients in Tripoli and has indicated that only one pregnant woman was positive for HEV infection with a seropositivity rate of 0.22% (1/450). In addition, no significant exposure to HEVassociated risk factors has been reported (9).…”
Section: Introductionmentioning
confidence: 99%
“…In our analysis high prevalence of 33/84 (39.28%) of anti-HEV IgG were observed in HD patients which is in accordance with Harrison et al findings ( 28 ). Ismail et al (2019) in the Lebanon have reported 37/171 HD patients including 22/96 (22.92%) males and 15/75 (20%) females showed positivity for anti HEV IgG ( 29 ). Mrzljak et al (2020) in Croatia have described the HEV IgG antibodies was detected in 110 (27.9%) HD patients.…”
Section: Discussionmentioning
confidence: 98%